Factors affecting visual field outcome post surgery in sellar region tumors : retrospective study - Sriram, Prabu Rau (2016)
Background Despite the broad category of differentials for sellar region, most of them present with similar clinical signs & symptoms. Headache & visual disturbance are among the frequently seen as presenting symptom. Visual field (VF) assessment is one of the crucial component of neuroophtalmologic assessment and Mean Deviation (MD) value from automated perimetry allows quantification of the visual field defect. We formulated a study to look into the factors that affect the visual field outcome after surgery. Methods All patients with sellar region tumor who has underwent surgery in Queen Elizabeth Hospital from July 2010 to July 2016 were retrospectively analysed through hospital notes. VF assessment via Humphrey visual assessment for these patient pre and post surgery were reviewed for MD value. Results Eighty four patients were recruited and out of them, 151 eyes were taken into analysis after excluding eyes with missing data. Mean age of patients were 45.4 years with 70.2% of them were male. Visual disturbance is the commonest presenting symptom with mean duration of symptom prior to surgery is 9.7 months. Majority of them were pituitary adenomas (75%) followed by sellar meningioma (19%), craniopharyngioma (4.8%), and rathke cleft cyst (1.2%). 70.9% of patients showed improvement in VF based on MD outcome. Mean MD for pre surgery and post surgery were -14.0dB and -12.4dB, respectively. Univariate analysis reveals younger age, female sex, shorter duration of symptom, pituitary adenoma, transsphenoidal approach, and transcranial approach favours improvement in VF. Multivariate analysis shows only shorter symptom duration, transphenoidal approach, and transcranial approach are significant for favourable VF outcome when other factors adjusted. Conclusion Symptom duration and surgical approach were independent factors that affects the visual field after surgery in patients with sellar region tumors.